BEHAVIOR OF BEEF TOMATO HYBRIDS IN GREENHOUSE UNDER DESERTIC CONDITIONS IN THE NORTHWEST OF SONORA. - Raul Leonel Grijalva Contreras; RubÃ©n MacÃas Duarte; FabiÃ¡n Robles Contreras (Tropical and Subtropical Agroecosystems, 2011)
The objective of this research was to evaluate the potential yield and fruit quality of 10 beef tomatoes hybrids using a low level technology greenhouse and desertic conditions of Northwest of Sonora. This experiment was done during two years 2005 and 2006 at the Experimental Station of Caborca, INIFAP. The yield reached during both years was of 25.2 kg m-2 but 89.1% of this production was harvested during February to May. The tomatoes hybrids with higher yield were Zuni, Gironda and Charleston with 31.1, 28.2 and 26.7 kg m-2, respectively; while Thomas, Rapsodie, Sedona and Beatrice were the lowest yield with 20.1, 22.4, 23.1 and 24.9 kg m-2, respectively. By other side, the hybrids with better fruit weight in both years were Sedona and Charleston with 211.3 and 209.8 and 194.7 grams fruit-1. Also, there were differences among tomatoes hybrids on physiological disorders susceptibility (fruit cracking and blossom end rot). For this reason, adequate selection of the tomatoes hybrid is a good alternative for increase yield and fruit quality and reduction of physiological disorders.